2017
DOI: 10.1103/physrevb.95.085202
|View full text |Cite
|
Sign up to set email alerts
|

Electron scattering in tantalum monoarsenide

Abstract: We report comprehensive studies of the single crystal growth and electrical transport properties for various samples of TaAs, the first experimentally confirmed inversion symmetry-breaking Weyl semimetal. The transport parameters for different samples are obtained through the fitting of the two band model and the analysis of Shubnikov de Haas oscillations. We find that the ratio factor of transport lifetime to quantum lifetime is intensively enhanced when the Fermi level approaches the Weyl node. This result i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 42 publications
16
112
0
Order By: Relevance
“…Normally, these two time scales are of the same order for most 3D materials 37 . However, experiments have shown that the ratio between transport lifetime and quantum lifetime is extremely large (∼ 10 2 ) for WSM1 40 when Fermi level approaches the Weyl nodes. Noticing that WSM2 possesses longer localization length (along the direction of tilt) and shorter quantum lifetime (see Fig.…”
Section: Self-consistent Born Approximationmentioning
confidence: 99%
“…Normally, these two time scales are of the same order for most 3D materials 37 . However, experiments have shown that the ratio between transport lifetime and quantum lifetime is extremely large (∼ 10 2 ) for WSM1 40 when Fermi level approaches the Weyl nodes. Noticing that WSM2 possesses longer localization length (along the direction of tilt) and shorter quantum lifetime (see Fig.…”
Section: Self-consistent Born Approximationmentioning
confidence: 99%
“…Angle resolved photoemission spectroscopy (ARPES) experiments revealed Fermi arcs on the surface and Weyl fermion cones and Weyl nodes in the bulk of the sample [5,7,8]. Furthermore, TaAs exhibits gigantic magnetoresitance of 5.4 × 10 4 % at 10 K upon application of a 9 T magnetic field, and a large mobility of 5 × 10 5 cm 2 ·V −1 ·s −1 [9]. Similar properties have also been reported in NbP, with magnetoresistance of 8.5 × 10 4 % at 2 K and 9 T, and mobility of 5 × 10 6 cm 2 ·V −1 ·s −1 [10].…”
Section: Introductionmentioning
confidence: 99%
“…(49) originate from the topological correction δj given by Eq. (20). Note also that the correction to the velocity δv stems from the oscillating magnetic field in the energy dispersion (32) and is equal to…”
Section: Collective Modes: General Considerationmentioning
confidence: 99%
“…In the following, therefore, we will assume that the field B 5 is weak or, in other words, thatà 5 is negligible compared to the chiral shift b. Then, it is justified to replace (19) and (20). It is worth noting that the topological correction (17) plays an important role even without pseudoelectromagnetic fields.…”
Section: The Consistent Chiral Kinetic Theorymentioning
confidence: 99%
See 1 more Smart Citation